Reexamining English Clay Pipes in Captive African Burials on the Island of Barbados. (1st September 2016) - Brown, Brittany
Abstract : Research in historical archaeology has often focused on analyzing the degree to which African diaspora material culture has been shaped by the beliefs and practices of particular African cultures impacted by the trans-Atlantic slave trade. Landscapes, architecture, and objects can, at times, be analyzed to evaluate whether their design, construction, or use has been influenced by such cultural traditions. Through the concepts of innovation and creolization, material culture such as this can be reinterpreted in new ways. This article reexamines English manufactured smoking pipes recovered from Newton Plantation cemetery on Barbados. I argue that within an African diasporic burial context, unmodified European manufactured objects, such as English manufactured smoking pipes, could carry cultural significance shaped by African cultural beliefs and practices. Artifacts such as these are embedded in both diversity and situational complexity.